Loading rate and holding load dependent room temperature nanoindentation creep behavior of 60NiTi alloy: Individual and coupling effects. (28th February 2022) - He, Wanjun; Zeng, Qunfeng; Yan, Chao; Zhu, Jianing; Zhang, Danli; Cao, Jiangnan
Highlights: Solution treated 60NiTi alloy has two main texture components of 1 ¯ 10 < 4 ¯ 4 ¯ 1> and 1 ¯ 10 < 1 ¯ 1 ¯ 4>, which is different from characteristic fiber textures of bcc alloys. There is no direct relationship between initial displacement and creep displacement. Creep displacement is dominated by strain rate at the onset of holding stage. Higher loading rate leads to higher strain rate at the onset of holding stage, while which is declined with increasing holding load or with simultaneously increasing loading rate and holding load. With holding time prolonged, the creep deformation mechanism can be changed from dislocation movement to diffusion creep. Abstract: 60NiTi alloy is highly promising for aerospace bearings and mechanisms. Shock load that is inevitably generated during launching process brings about an quick loading process and transient load duration, and may further results in an unnoticed but detrimental creep deformation. On this account, the nanoindentation creep behavior of solution-treated 60NiTi alloy at room temperature and the corresponding influencing mechanism were studied. The results show that creep displacement was dominated by strain rate at the very beginning of holding stage. Strain rate and flow stress at the very beginning of holding stage were increased with an increased loading rate but declined with increasing holding load or with simultaneously increasing loading rate and holding load. The underlying mechanisms were provided as nucleation and absorption of geometrically necessary dislocations (GNDs) associated with strain gradient plasticity theory rather than the model based on the consumption of creep deformation at loading stage.